Аристотеловске схолије у српскословенском преводу „Аподиктичких слова о исхођењу Светог Духа” Григорија Паламе. - КНЕЖЕВИЋ, МИКОЊА (Bulletin of the Institute of Ethnography of the Serbian Academy of Sciences & Arts / Glasnik Etnografskog Instituta SANU, 2024)
The Serbian Church-Slavonic translation of Gregory Palamas' "Apodictic Treatises on the Procession of the Holy Spirit" was made around 1360. The autograph of this translation, preserved in Codex 88 of the monastery Dečani, contains significant number of scholia, which help us additionally to follow the process of translating and commenting of Palamas' basic text. In this paper I will focuss on two of those scholia which reveal the philosophical thread of Palamas' (theological) argumentation - first of all, the Aristotelian one. After the basic information on the significance of the Serbian Church-Slavonic translation of Palamas' "Apodictic Treatises" is provided, these scholia are given in the original and translation into Modern Serbian, being also accompanied by our comments and clarifications.